Clinical epidemiological profile of cases of tuberculosis - HIV coinfection (Research, Society and Development, 2022)
It is estimated that people who have tuberculosis are more susceptible to developing HIV. This association can increase the death rate, since with the co-infection there can be remodeling in each infection and in the resulting diseases, undergoing changes that course the clinical picture, being unfavorable to treatment and prognosis. The present study analyzed the clinical and epidemiological aspects of tuberculosis-HIV (TB-HIV) co-infection cases in the state of Tocantins, in addition to knowing the incidence between sex, age group and period of time. This is a descriptive, exploratory study, carried out using data extracted from the SUS Informatics System database (DATASUS) from 2017 to 2021, comparing the period of time, sex and age groups. From the data extracted, it was possible to observe that in the period from 2017 to 2021, 1146 cases of tuberculosis were reported in the state of Tocantins, of which 97 were positive for TB-HIV co-infection. In view of the results found, the most affected gender was male, the age group with the most reported cases was between 20 and 39 years and the most prevalent race for tuberculosis and for the co-infection was brown. In Tocantins, during the period studied, the profile of individuals who presented TB-HIV co-infection alerts to the need for public policies of health promotion and education directed mainly at men's health in an economically active age group.